ANALISIS PERBANDINGAN KINERJA KEUANGAN PERBANKAN SYARIAH (STUDI BANK MUAMALAT DAN BANK SYARIAH INDONESIA) - Muhammad Ananda Rafli; Arsa; Efni Anita (Fakultas EKonomi dan Bisnis Islam UIN Sulthan Thaha SAifuddin Jambi, 2025)
Bank performance will show a company's ability to manage and allocate its resources, so that every bank definitely wants to have good performance to be able to survive in the midst of increasingly tight banking industry turmoil. Financial performance assessment can be analyzed using ratio analysis that focuses on factors: capital, quality of productive assets, management, profitability and liquidity. This study has research results that the comparison of the CAR ratio at Muamalat Bank and Indonesian Sharia Bank in 2017-2022 shows that there is no difference between the CAR ratio at Bank Muamalat and Bank Syariah Indonesia. As evidenced by the Sig value (0.152)> 0.05. The comparison of the NPF ratio at Muamalat Bank and Indonesian Sharia Bank in 2017-2022 shows that there is no difference between the NPF ratio at Bank Muamalat and Bank Syariah Indonesia. As evidenced by the Sig value (0.134)> 0.05. Comparison of ROA ratios at Muamalat Bank and Indonesian Sharia Bank in 2017-2022 shows that there is a difference between the ROA ratio at Bank Muamalat and Bank Syariah Indonesia. As evidenced by the Sig value (0.00) > 0.05. Comparison of BOPO ratios at Muamalat Bank and Indonesian Sharia Bank in 2017-2022 shows that there is a difference between the BOPO ratio at Bank Muamalat and Bank Syariah Indonesia. As evidenced by the Sig value (0.00) > 0.05. Comparison of FDR ratios at Muamalat Bank and Indonesian Sharia Bank in 2017-2022 shows that there is a difference between the FDR ratio at Bank Muamalat and Bank Syariah Indonesia. As evidenced by the Sig value (0.00) > 0.05.